Longer survival in patients with human papillomavirus–related head and neck cancer after positive postradiation planned neck dissection. Issue 7 (25th September 2014) - Huang, Shao Hui; Patel, Samip; O'Sullivan, Brian; Shen, Xiaowei; Xu, Wei; Weinreb, Ilan; Perez–Ordonez, Bayardo; Irish, Jonathan; Waldron, John; Gullane, Patrick; Gilbert, Ralph; Brown, Dale; et al.
ABSTRACT Background The purpose of this study was to compare outcomes between human papillomavirus (HPV)‐related versus ‐unrelated head and neck cancer after pathological positive planned neck dissection. Methods Positive planned neck dissection for head and neck cancers from 1998 to 2010 were included in this study. Outcomes after planned neck dissection were compared between HPV‐related versus ‐unrelated cohorts. Multivariate analysis identified survival predictors. Results HPV‐related head and neck cancer (n = 32) had better 5‐year overall survival (48% vs 27%; p = .021), marginally lower second malignancy (7% vs 16%; p = .13), but similar local, regional, and distant control (87% vs 89%; 94% vs 89%; 62% vs 58%, respectively) versus HPV unrelated (n = 38). HPV status conferred reduced risk of death (hazard ratio [HR], 0.5; p = .038) after adjusting for age, smoking, and initial T and N classifications. Conclusion This study reveals that positive planned neck dissection for HPV‐related head and neck cancer represents a biologic unfavorable subset of the HPV population with unsatisfactory survival attributable to distant metastasis. The longer survival compared to the HPV‐unrelated counterpart is likely related to a marginally lower second malignancy rather than better disease control. © 2014 Wiley Periodicals, Inc. Head Neck 37: 946–952, 2015